Mechanism of Action of Small-Molecule Agents in Ongoing Clinical Trials for SARS-CoV-2: A Review - Zhao, Lei; Li, Song; Zhong, Wu (Frontiers in Pharmacology, 2022)
Since the first reports from December 2019, COVID-19 caused an overwhelming global pandemic that has affected 223 countries, seriously endangering public health and creating an urgent need for effective drugs to treat SARS-CoV-2 infection. Currently, there is a lack of safe, effective, and specific therapeutic drugs for COVID-19, with mainly supportive and symptomatic treatments being administered to patients. The preferred option for responding to an outbreak of acute infectious disease is through drug repurposing, saving valuable time that would otherwise be lost in preclinical and clinical research, hastening clinical introduction, and lowering treatment costs. Alternatively, researchers seek to design and discover novel small-molecule candidate drugs targeting the key proteins in the life cycle of SARS-CoV-2 through an in-depth study of the infection mechanism, thus obtaining a number of candidate compounds with favorable antiviral effects in preclinical and clinical settings. There is an urgent need to further elucidate the efficacy and mechanism of action of potential anti-SARS-CoV-2 small-molecule drugs. Herein, we review the candidate small-molecule anti-SARS-CoV-2 drugs in ongoing clinical trials, with a major focus on their mechanism of action in an attempt to provide useful insight for further research and development of small-molecule compounds against SARS-CoV-2 infection.